(untitled) (Costa Rican Journal of Guidance & Counseling, 2025)
Objective: To describe and analyze the demands of ninth-grade students related to educational and career guidance at the Instituto Profesional Técnico Leonila Pinzón de Grimaldo and the Instituto Profesional Técnico e Industrial de Aguadulce, in Coclé, Panama, during the second semester of 2023. Methodology: A basic, non-experimental, cross-sectional, retrospective, and quantitative study was conducted. This study was based on fieldwork through the administration of a structured survey to 60 students. The survey was validated. Descriptive statistics were presented, and analysis was performed using the chi-square test. Results: Ninth-grade students articulated specific demands for educational guidance, emphasizing the need for support in personal, social, and vocational aspects. They expressed a preference for the use of Information and Communication Technologies (ICTs) and dynamic, interactive, and personalized guidance modalities. Conclusions: Educational guidance faces the challenge of adapting to a complex environment, where the significant incorporation of ICTs requires not only infrastructure but also the development of professional skills in guidance providers. Overcoming these limitations would allow for optimizing interventions and expanding the formative impact on the development of academic and professional careers.